A pedagogical experience of the Progressive Education movement: Carmen Conde and the Orfanato Nacional de El Pardo (Spanish National Orphanage of El Pardo) - Fernández Fernández, Javier (Historia y Memoria de la Educación, 2019)
This article analyzes the work done by Carmen Conde at the Orfanato Nacional de El Pardo (Spanish National Orphanage of El Pardo) as inspector-overseer of studies between October of 1934 and September of 1935. Firstly, the article explains the transformation that this center had undergone in the early years of the Second Spanish Republic and examines the appointment of Carmen Conde at the Orphanage, her educational initiatives and the conflictive relationship with the management positions of the organization, the board and the administrator, until her removal in the summer of 1935. Secondly, the article studies her attempts to return to the Orphanage after the electoral triumph of the Popular Front during the winter of 1936 and the competition with María Teresa Junquera to lead the institution. Thirdly, the text exposes the circumstances of the creation and the content of her publication La composición literaria infantil: (escuela primaria) (Literary creation for children: primary school), as a result of her attempts carried out in the Orfanato Nacional de El Pardo to improve the oral and written expression of the foster children. Finally, the paper enquires into this work and compares it to the second version of the thirty characteristics of the New Schools elaborated by Adolphe Ferrière in 1925. These characteristics have to do with the organization of the schools, physical life, intellectual life, social education and artistic and moral education.